2015
DOI: 10.1176/appi.ps.201400134
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and Facilitators in the Implementation of Cognitive-Behavioral Therapy for Youth Anxiety in the Community

Abstract: Objective The study examined, from the perspective of therapists, the barriers to and facilitators in implementing cognitive-behavioral therapy (CBT) for anxious youths in community settings. Methods Fifty therapists (43% of the original training sample of 115 providers) participated in a follow-up interview two years after training and consultation. They reported on barriers to and facilitators in implementation of CBT for youths with anxiety. Results Qualitative analyses identified numerous barriers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
52
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 37 publications
3
52
2
Order By: Relevance
“…This finding diverges from other literature documenting the impact of intervention characteristics (Ringle et al, 2015) and intervention-setting fit (Damschroder et al, 2009; Green & Aarons, 2011; Lyon et al, 2014; Sackett et al, 1996). However, this may have to do with who was queried about implementation barriers; as well as our specific focus on inner and outer context factors in the interview guide.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding diverges from other literature documenting the impact of intervention characteristics (Ringle et al, 2015) and intervention-setting fit (Damschroder et al, 2009; Green & Aarons, 2011; Lyon et al, 2014; Sackett et al, 1996). However, this may have to do with who was queried about implementation barriers; as well as our specific focus on inner and outer context factors in the interview guide.…”
Section: Discussioncontrasting
confidence: 99%
“…These studies have identified a host of barriers and facilitators at the individual therapist level (e.g., attitudes and training; Pagoto et al, 2007; Palinkas et al, 2008; Stirman et al, 2013); organizational level (e.g., organizational structure and support; Langley, Nadeem, Kataoka, Stein, & Jaycox, 2010; Ringle et al, 2015); intervention level (e.g., structure; Ringle et al, 2015) and system level (e.g., social networks; Palinkas et al, 2011). Although these studies have provided important insights about barriers and facilitators to implementation, most of the studies only interviewed therapists (for an exception, see Palinkas et al, 2011) and did not interview different stakeholder groups involved in the implementation process such as agency leaders, system leaders, and treatment developers.…”
mentioning
confidence: 99%
“…In contrast to CBT, other orientations view what happens in session over what happens outside of session (e.g., homework) as the mechanism of change. Third, some research suggests that clinicians view homework as unrealistic for some families with high levels of outside stressors (Ringle et al, 2015). Finally, our speculation is that homework planning and review typically receive too little attention in training and consultation and need more targeted initial training and ongoing support to increase effective use.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, prior work examining facilitators of EBP use more broadly have found both clinician factors, such as more positive attitudes toward EBP, and organizational variables, such as organizational culture and climate, to be associated with greater EBP use (Aarons, 2004; Beidas et al, 2015; Brookman-Frazee, Haine, Baker-Ericzen, Zoffness, & Garland, 2010). When barriers to exposure have been examined, data indicate that barriers to clinician use of exposure similarly arise across these multiple levels, and include negative clinician attitudes (Deacon et al, 2013), a lack of time to prepare for exposures (Farrell, Deacon, Dixon, & Lickel, 2013), little access to needed materials, and few trained supervisors (Ringle et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, we examined whether clinicians who had participated in an evidence-based practice initiative that included some aspect of training in exposure (i.e., the Beck Community initiative [Creed, Wolk, Feinberg, Evans, & Beck, 2016], the Philadelphia Alliance for Child Trauma Services [Beidas et al, 2016], and Prolonged Exposure [Foa et al, 2005]) were more likely to use exposure for anxiety relative to those clinicians who did not participate. As lack of preparation time has been a cited barrier to exposure (e.g., (Ringle et al, 2015), we also examined clinician caseload size. We anticipated that positive attitudes, greater knowledge, fewer years of experience, a lower caseload, and participation in an EBP initiative would be associated with greater use of exposure for anxiety.…”
Section: Introductionmentioning
confidence: 99%